Comparison of Required Competences and Task Material in Modeling Education - Soyka, Chantal; Ullrich, Meike; Striewe, Michael; Schaper, Niclas (Enterprise Modelling and Information Systems Architectures)
The reform of the European academic landscape with the introduction of bachelor's and master's degree programs has brought about several profound changes for teaching and assessment in higher education. With regard to the examination system, the shift towards output-oriented teaching is still one of the most significant challenges. Assessments have to be integrated into the teaching and learning arrangements and consistently aligned towards the intended learning outcomes. In particular, assessments should provide valid evidence that learners have acquired competences that are relevant for a specific domain. However, it seems that this didactic goal has not yet been fully achieved in modeling education in computer science. The aim of this study is to investigate whether typical task material used in exercises and exams in modeling education at selected German universities covers relevant competences required for graphical modeling. For this purpose, typical tasks in the field of modeling are first identified by means of a content-analytical procedure. Subsequently, it is determined which competence facets relevant for graphical modeling are addressed by the task types. By contrasting a competence model for modeling with the competences addressed by the tasks, a gap was identified between the required competences and the task material analyzed. In particular, the gap analysis shows the neglect of transversal competence facets as well as those related to the analysis and evaluation of models. The result of this paper is a classification of task types for modeling education and a specification of the competence facets addressed by these tasks. Recommendations for developing and assessing student's competences comprehensively are given.
Keywords: conceptual modeling; higher education; competence-oriented assessment; task analysis; graphical modeling

Die Doppelwirkung von Information für klimafreundliches Handeln - Frick, Marc; Foese, Dario; Von Graevenitz, Kathrine; Kesternich, Martin; Wagner, Ulrich
Informationen sind für eine erfolgreiche Klimapolitik in doppelter Hinsicht wichtig: Sie werden benötigt, wenn Potenziale zur Vermeidung von Emissionen identifiziert und klimapolitische Instrumente ausgewählt werden. Und sie sind zentral, damit Bürger/innen selbst Entscheidungen im Sinne des Klimaschutzes treffen können.
Keywords: General Medicine

Implementing Digital Responsibility through Information Systems Research: A Delphi Study of Objectives, Activities, and Challenges in IS Research - Beverungen, Daniel; zur Heiden, Philipp; Lehrer, Christiane; Trier, Matthias; Bartelheimer, Christian; Bradt, Tobias; Distel, Bettina; Drews, Paul; Ehmke, Jan Fabian; Fill, Hans-Georg; Flath, Christoph M.; Fridgen, Gilbert; et al.

Methodical Approach to Reducing Design Time by using Neural Networks in Early Stages of Concept Development - Ott, Manuel; Meihöfener, Niclas; Mozgova, Iryna (Proceedings of the 34rd Annual International Solid Freeform Fabrication Symposium 2023)
Modern companies often face various challenges in concept development of products or systems. Design engineers prepare initial concepts as 3D models. These are then simulated by computational engineers. If requirements are not met, this necessitates an iterative process that runs between the design and computation departments until a valid concept is created. Design methods such as topology optimization are often used here. The upcoming result is then attempted to be adapted to certain manufacturing processes. These iteration loops can sometimes take a very long time, since the model construction and structural optimization generate large computational efforts. The present work shows on an example a methodical approach, which represents a first proof of concept, to solving this problem, including a description of methods and techniques, as well as possible problems in a detailed analysis concerning training data for neural networks and their abstraction capabilities. It is evident that additional research work needs to be conducted for further utilization in order to address all arising questions.

Aushandlungen von Inklusion und Exklusion im Kontext der (nicht-)Verfügbarkeit mobiler Medien. Ein rekonstruktiver Blick auf die Mediatisierung berufsschulischer Möglichkeitsräume. - Dehmel, Lukas; Meister, Dorothee (Jahrbuch Medienpädagogik 20. Inklusive Medienbildung in einer mediatisierten Welt. Medienpädagogische Perspektiven auf ein interprofessionelles Forschungsfeld.)

Quasi-In Situ Localized Corrosion of an Additively Manufactured FeCo Alloy in 5 Wt Pct NaCl Solution - Pramanik, Sudipta; Krüger, Jan Tobias; Schaper, Mirko; Hoyer, Kay-Peter (Metallurgical and Materials Transactions A)
Abstract FeCo alloys are important materials used in pumps and motors in the offshore oil and gas drilling industry. These alloys are subjected to marine environments with a high NaCl concentration, therefore, corrosion and catastrophic failure are anticipated. So, the surface dissolution of additively manufactured FeCo samples is investigated in a quasi- in situ manner, in particular, the pitting corrosion in 5.0 wt pct NaCl solution. The local dissolution of the same sample region is monitored after 24, 72, and 168 hours. Here, the formation of rectangular and circular pits of ultra-fine dimensions (less than 0.5 µ m) is observed with increasing immersion time. In addition, the formation of a corrosion-inhibiting surface layer is detected on the sample surface. Surface dissolution leads to a change in the surface structure, however, no change in grain shape or grain size is noticed. The surface topography after local dissolution is correlated to the grain orientation. Quasi- in situ analysis shows the preferential dissolution of high-angle grain boundaries (HAGBs) leading to a change in the fraction of HAGBs and low-angle grain boundaries fraction (LAGBs). For the FeCo sample, a potentiodynamic polarisation test reveals a corrosion potential (E corr ) of − 0.475 V referred to the standard hydrogen electrode (SHE) and a corrosion exchange current density (i corr ) of 0.0848 A/m 2 . Furthermore, quasi- in situ experiments showed that grains oriented along certain crystallographic directions are corroding more compared to other grains leading to a significant decrease in the local surface height. Grains with a plane normal close to the $$\langle {1}00\rangle$$ ⟨ 100 ⟩ direction reveal lower surface dissolution and higher corrosion resistance, whereas planes normal close to the $$\langle {11}0\rangle$$ ⟨ 110 ⟩ direction and the $$\langle {111}\rangle$$ ⟨ 111 ⟩ direction exhibit a higher surface dissolution.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Schulpraktikum zwischen Kind und Nebenjob? Einfluss von sozialen und organisationalen Bedingungsfaktoren auf das Belastungserleben Lehramtsstudierender im Praxissemester - Vogelsang, Christoph; Brandhorst, André (Herausforderung Lehrer* Innenbildung-Zeitschrift Zur Konzeption, Gestaltung Und Diskussion)
Trotz der Annahme, dass Langzeitpraktika im Lehramts-studium hohe Belastungen für Studierende darstellen können, sind empirische Analysen zum Einfluss sozialer (z.B. die Betreuung eigener Kinder, Pflegeaufgaben) und organisationaler Bedingungsfaktoren (z.B. Erwerbstätigkeit, Fahrzeiten zur Praktikumsschule, Zusatzkosten) rar. Daher wurden in diesem Beitrag im Rahmen einer Sekundäranalyse evaluativer Daten Zusammenhänge zwischen dem Belastungserleben von N = 611 Lehramtsstudierenden im Praxissemester an der Universität Paderborn und verschiedenen Bedingungsfaktoren untersucht. Das Belastungserleben wurde vor und nach dem Praxissemester mit Hilfe des Maslach-Burnout-Inventars (MBI-SS) erfasst. Regressionsanalysen ergaben, dass soziale und organisationale Bedingungsfaktoren kaum Unterschiede im Belastungserleben aufklären. Als einzige bedeutende Faktoren mit kleinen Effekten erwiesen sich die Fahrzeit zur Praktikumsschule und die Höhe evtl. zusätzlicher Materialkosten. Auch durch Clusteranalysen ermittelte Gruppen von hochbelasteten Studierenden zeichnen sich nicht durch spezifische soziale oder organisationale Bedingungsfaktoren aus.
Keywords: Praxissemester; Belastung; Burnout; Lehramtsstudium; soziale Situation

The Origination of Online Reviews in B2B Markets: A Qualitative Study on the Underlying Motives of Review Writers - Seutter, Janina

Frontal theta reveals further information about neural valence‐dependent processing of augmented feedback in extensive motor practice - A secondary analysis - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (European Journal of Neuroscience)
Abstract Supplementing an earlier analysis of event‐related potentials in extensive motor learning (Margraf et al., 2022a, 2022b), frontal theta‐band activity (4–8 Hz) was scrutinized. Thirty‐seven participants learned a sequential arm movement with 192 trials in each of five practice sessions. Feedback, based on a performance adaptive bandwidth, was given after every trial. Electroencephalogram (EEG) was recorded in the first and last practice sessions. The degree of motor automatization was tested under dual‐task conditions in a pre‐test–post‐test design. Quantitative error information was transported in both feedback conditions (positive and negative). Frontal theta activity was discussed as a general signal that cognitive control is needed and, therefore, was expected to be higher after negative feedback. Extensive motor practice promotes automatization, and therefore, decreased frontal theta activity was expected in the later practice. Further, it was expected that frontal theta was predictive for subsequent behavioural adaptations and the amount of motor automatization. As the results show, induced frontal theta power was higher after negative feedback and decreased after five sessions of practice. Moreover, induced theta activity was predictive for error correction and, therefore, an indicator of whether the recruited cognitive resources successfully induced behavioural adaptations. It remains to be solved why these effects, which fit well with the theoretical assumptions, were only revealed by the induced part of frontal theta activity. Further, the amount of theta activity during practice was not predictive for the degree of motor automatization. It seems that there might be a dissociation between attentional resources associated with feedback processing and attentional resources associated with motor control.
Keywords: General Neuroscience

Frontal theta reveals further information about neural valence-dependent processing of augmented feedback in extensive motor practice. - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Mobile Electroencephalography Reveals Differences in Cortical Processing During Exercises With Lower and Higher Cognitive Demands in Preadolescent Children - Becker, Linda; Büchel, Daniel; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatric Exercise Science)
Purpose : The aim of this study was to examine whether cortical activity changes during exercise with increasing cognitive demands in preadolescent children. Method : Twenty healthy children (8.75 [0.91] y) performed one movement game, which was conducted with lower and higher cognitive demands. During a baseline measurement and both exercise conditions, cortical activity was recorded using a 64-channel electroencephalographic system, and heart rate was assessed. Ratings of perceived excertion and perceived cognitive engagement were examined after each condition. To analyze power spectral density in the theta, alpha-1, and alpha-2 frequency bands, an adaptive mixture independent component analysis was used to determine the spatiotemporal sources of cortical activity, and brain components were clustered to identify spatial clusters. Results : One-way repeated-measures analyses of variance revealed significant main effects for condition on theta in the prefrontal cluster, on alpha-1 in the prefrontal, central, bilateral motor, bilateral parieto-occipital, and occipital clusters, and on alpha-2 in the left motor, central, and left parieto-occipital clusters. Compared with the lower cognitive demand exercise, cortical activity was significantly higher in theta power in the prefrontal cluster and in alpha-1 power in the occipital cluster during the higher cognitive demand exercise. Conclusion : The present study shows that exercise complexity seems to influence cortical processing as it increased with increasing cognitive demands.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Pediatrics; Perinatology and Child Health

Spielplatzgeräte: Potenziale zur ganzheitlichen Förderung von Heranwachsenden - Strotmeyer, Anne; Ortwein, Lena; Kehne, Miriam (Playground@Landscape)

The science of deceptive human movement - Güldenpenning, Iris; Jackson, Robin C.; Cañal-Bruland, Rouwen (Human Movement Science)

Learning and Memory in Sports - Weigelt, Matthias; Krause, Daniel; Güldenpenning, Iris (Sport and Exercise Psychology)

Superstructure-dependent stability of DNA origami nanostructures in the presence of chaotropic denaturants - Hanke, Marcel; Dornbusch, Daniel; Tomm, Emilia; Grundmeier, Guido; Fahmy, Karim; Keller, Adrian (Nanoscale)
The structural stability of DNA origami nanostructures in various chemical environments is an important factor in numerous applications, ranging from biomedicine and biophysics to analytical chemistry and materials synthesis. In...
Keywords: General Materials Science

Routing in Hypergraphs - Deppe, Volker

Parallele Universen des Wissenschaftsmanagements? Ein Vergleich des Wissenschaftsmanagements an Hochschulen und außeruniversitären Forschungseinrichtungen in Deutschland. - Schneider, Sebastian; Mauermeister, Sylvi; Henke, Justus; Aust, Robert (Hochschulmanagement. Zeitschrift für die Leitung, Entwicklung und Selbstverwaltung von Hochschulen und Wissenschaftseinrichtungen.)
The development of good conditions for research is an essential task of research institutions, which in practice is nowadays mostly performed by science managers. Research in the field of science management in Germany mainly refers to developments at universities, whereas little is known about the situation at so called non-university research organisations. At the same time, there are hardly any statistics on the size of the science management in Germa-ny. In order to take first steps towards exploring these parallel universes, this article presents a comparative mapping of science management at universities and non-university research organisations for Germany by drawing on a special analysis of the German Federal Statistical Office and an online survey.

Citizen Science: Laien-Partizipation an Forschung - Göbel, Claudia; Henke, Justus; Mauermeister, Sylvi; Pasternack, Peer (Wissenschaftskommunikation, neu sortiert.)

Gesellschaftlich-demokratische Teilhabe: trotz hochschulischer oder durch hochschulische Bildung? - de Angelis, Moira; Harles, Dorothea; Mauermeister, Sylvi; Aust, Robert (Das Hochschulwesen)

Multirate Discrete Mechanics and Optimal Control for a Flexible Satelite Model - Lishkova, Yana; Ober-Blöbaum, Sina; Leyendecker, Sigrid